THE EFFECTIVENESS OF THE SOCIO-SCIENTIFIC BASED CIRC (COOPERATIVE, INTEGRATED, READING AND COMPOSITION) MODEL ON STUDENTS' CURIOSITY - Hayawati, Nita Elia; Faizah, Ulinnuha Nur (Science Education, Institut Agama Islam Negeri Ponorogo, 2023)
One of the characters that must be developed in students is curiosity, namely the desire to know more deeply and broadly about something that is learned, seen or heard. This research aims to determine the effectiveness of the socio-scientific based CIRC model on Students’ Curiosity. The CIRC model is cooperative learning that integrates reading and writing activities using a socio-scientific approach which is new to research. This research uses a quasi-experimental quantitative method. The sample consisted of 25 students as the experimental class and 25 students as the control class. Data collection techniques use tests and observation sheets which are analyzed descriptively quantitatively and inferential statistics. The results of the independent sample t-test produce a P-Value of 0.000, if the P-Value <α = 5% (0.05), then H0 is rejected, meaning there is a significant difference between the curiosity of experimental class and control class students. The results of the one tailed t-test produced a P-Value of 0.000 so that H0 was rejected and the estimated value for difference was 10.80, so the curiosity of experimental class students was better than that of the control class. The ANCOVA test shows a significance of 0.000<α=(0.05), meaning that the socio-scientific based CIRC model is declared effective in increasing curiosity. It can be concluded that the curiosity of students who use the socio-scientific based CIRC model is more effective than those who use the socio-scientific based non CIRC model.